Factors associated with growth status among toddlers with medical conditions at a selected outpatient pediatric clinic - Naharuddin, Nurliyana (2019)
This cross-sectional study aimed to investigate the factors associated with growth status among toddlers with medical conditions in outpatient clinic pediatric in Hospital Serdang, Selangor. A total of 152 toddlers aged 12-36 months were recruited using a purposive sampling method. A questionnaire consisted of socio-demographic, medical background, eating behavior and parental feeding practices were assessed. Weight and height of the subjects were measured and the growth status was compared with WHO growth chart. The cut-off values for underweight, stunting and wasting were <-2SD. Toddlers in healthy growth status (non-underweight or non-stunting or non-wasting) was defined as the cut-off point were >-2 SD to <+2 SD. Dietary intakes were measured using 3-day food record. Mean age of the respondents was 23.33 ± 4.77 months. The prevalence of underweight, stunting, and wasting was 25%, 30.3%, and 17.8% respectively. More than half (56.6%) aged between 12 and 24 months and about 42.8% of the respondents were the only child in the family. The household income was mostly above RM3001 (60.5%) indicate moderate household income. Both parents attained at least a tertiary education and more than half of the mothers were also working (59.2%). As compared to non-underweight respondents, the underweight had more girls, lower birth weight, born pre-termed and had a caesarean delivery, had more frequent intake of juices, cordial drink, and carbonated drink, preferred more cereals, vegetables, fruits, and beverages and had lower energy intake compared to non-underweight respondents. Parents with underweight respondents used encouraging practice, less monitoring, pressure-to-eat and more restrictive than those parents of non-underweight respondents. As compared to nonstunting respondents, the stunting had more girls, aged between 25 and 36 months, lower birth weight, born as pre-termed and had a caesarean delivery. Stunting respondents had a higher score of feeding problem and had more frequent intake of juices, carbonated drink and tea, preferred cereals, dairy, fruits, tuber, desserts, and had lower energy, protein and lower fat intakes as compared to non-stunting respondents. Parents of the stunting respondents used less monitoring and pressure-to-eat practices than those parents of nonstunting respondents. As compared to non-wasting respondents, wasting respondents had more than one siblings, lower birth weight, had no feeding problems and prefer more cereals, vegetables, fruits, and beverages than those non-wasting respondents. Parents of wasting respondents used encouragement but less monitoring than those parents of non-wasting respondents. In underweight, the higher the birth weight, frequent used of monitoring practices and the higher energy intake were the factors that were protective against underweight. In stunting, the age group between 25-36 months old, had a higher numbers of siblings and being pressured-to-eat were more likely to be associated with stunting but the higher the birth weight, frequent used of monitoring practices and the higher energy intake were protective against stunting. In wasting, the higher the number of siblings were more likely to be associated with wasting. Meanwhile, frequent used of monitoring was protective against wasting. The findings suggest that the factors that associated with undernutrition (underweight, stunting and wasting) were different for each indicators of undernutrition. However, parental feeding practice of monitoring was consistently associated with all the indicators among toddlers with medical conditions. Therefore, assessment and interventions should also involve education and guidance on appropriate child feeding practices to parents of toddlers with medical conditions to maintain their healthy growth status.